2008
DOI: 10.1007/s11741-008-0414-1
|View full text |Cite
|
Sign up to set email alerts
|

Rolling contact fatigue of silicon nitride bearing balls under pure rolling condition

Abstract: A newly developed pure rolling fatigue test rig with three contact points for bearing balls was used to perform rolling contact fatigue (RCF) tests. The fatigue properties of GCr15 steel balls and two kinds of Si3N4 ceramic balls produced with different technologies were compared. Ball surfaces were examined after failure with optical microscope and scanning electron microscope (SEM). It was identified by tests that the failure mode of ceramic balls was surface spall. The main factor of ceramic ball failure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Generally, ceramic ball's rolling contact fatigue life is used to evaluate whether it can be used in rolling bearing, at present, as a new bearing ball fatigue life test rig: fatigue life test rig for ball with three point contact, it can not only test the traditional steel ball, but also ceramic ball [2] .The tested ball is forced by enlarged testing load by lever structure via driving roller, the driving roller has sunken arc, the tested ball is supported by the two escorting rollers, at the same time, the two escorting rollers are supported by guiding roller and supporting roller, thus, the test rig can work normally by external electromotor through the pulleys transmission, and rotating parts will produce eccentric mass due to uneven distribution of the quality, thus produce exciting force. The exciting frequency is equal to the rotating frequency [3] ; And sensor is on the cover of the testing rig, thus can obtain the output signal.…”
Section: Fatigue Life Test Rig For Ball With Three Point Contactmentioning
confidence: 99%
“…Generally, ceramic ball's rolling contact fatigue life is used to evaluate whether it can be used in rolling bearing, at present, as a new bearing ball fatigue life test rig: fatigue life test rig for ball with three point contact, it can not only test the traditional steel ball, but also ceramic ball [2] .The tested ball is forced by enlarged testing load by lever structure via driving roller, the driving roller has sunken arc, the tested ball is supported by the two escorting rollers, at the same time, the two escorting rollers are supported by guiding roller and supporting roller, thus, the test rig can work normally by external electromotor through the pulleys transmission, and rotating parts will produce eccentric mass due to uneven distribution of the quality, thus produce exciting force. The exciting frequency is equal to the rotating frequency [3] ; And sensor is on the cover of the testing rig, thus can obtain the output signal.…”
Section: Fatigue Life Test Rig For Ball With Three Point Contactmentioning
confidence: 99%
“…In terms of experiments, Zhou [24] designed a novel RCF experimental device and concluded that the primary mode of failure in ceramic bearings was material spalling due to crack propagation. Khan et al [25][26][27][28] and Wang et al [29,30] conducted numerous experimental studies utilizing four-ball and other RCF experimental devices, yielding a plethora of valuable conclusions.O.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have addressed the issue of strength and ring crack initiation [2][3][4], crushing [5,6], and the tensile fracture of a notched ceramic ball [7] under quasi-static loading, as well as the rolling contact fatigue strength properties [8][9][10][11][12][13][14][15][16][17][18][19] at room and high temperatures. On the other hand, many studies have addressed the fracture behavior, fracture strength properties, and the evaluation of monolithic ceramics subjected to thermal shock [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%